Defence diplomacy in ASEAN : running in circles? - Laksmana, Evan A. (2021)
Defence multilateralism through the ADMM and ADMM-Plus remains focused on diplomatic processes, rather than shaping strategic outcomes. Is it time for regional policymakers to review this?